Lys49 myotoxins, secreted phospholipase A2-like proteins of viperid venoms: a comprehensive review - Lomonte, Bruno (2023)
Muscle necrosis is a potential clinical complication of snakebite envenomings, which in severe cases can lead to functional or physical sequelae such as disability or amputation. Snake venom proteins with the ability to directly damage skeletal muscle fibers are collectively referred to as myotoxins, and include three main types: cytolysins of the “three-finger toxin” protein family expressed in many elapid venoms, the so-called “small” myotoxins found in a number of rattlesnake venoms, and the widespread secreted phospholipase A2 (sPLA2) molecules. Among the latter, protein variants that conserve the sPLA2 structure, but lack such enzymatic activity, have been increasingly found in the venoms of many viperid species. Intriguingly, these sPLA2-like proteins are able to induce muscle necrosis by a mechanism independent of phospholipid hydrolysis. They are commonly referred to as “Lys49 myotoxins” since they most often present, among other substitutions, the replacement of the otherwise invariant residue Asp49 of sPLA2s by Lys. This work comprehensively reviews the historical developments and current knowledge towards deciphering the mechanism of action of Lys49 sPLA2-like myotoxins, and points out main gaps to be filled for a better understanding of these multifaceted snake venom proteins, to hopefully lead to improved treatments for snakebites.